Quantum rotation gates with controlled nonadiabatic evolutions. (15th March 2018) - Abdelrahim, Abdelrahman A H; Benmachiche, Abderrahim; Mahmoud, Gharib Subhi; Messikh, Azeddine
Abstract: Quantum gates can be implemented adiabatically and nonadiabatically. Many schemes used at least two sequentially implemented gates to obtain an arbitrary one-qubit gate. Recently, it has been shown that nonadiabatic gates can be realized by single-shot implementation. It has also been shown that quantum gates can be implemented with controlled adiabatic evolutions. In this paper, we combine the advantage of single-shot implementation with controlled adiabatic evolutions to obtain controlled nonadiabatic evolutions. We also investigate the robustness to different types of errors. We find that the fidelity is close to unity for realistic decoherence rates.